PENGARUH GREEN MARKETING TERHADAP GREEN BEHAVIOUR PADA PENGGUNA FITUR POHON KOLEKTIF GOGREENER GOJEK DENGAN MINAT KONSUMEN SEBAGAI VARIABEL MODERATING - Ika Novitasari; Novi Marlena (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
The purpose of this study is to determine the effect of green marketing, green behavior, and consumer interest in users of Gojek's GoGreener Collective Tree Feature. The population in this study were all users who had used Gojek's GoGreener Collective Tree Feature. The sample consists of 120 respondents. The sampling technique uses a non-probability sampling technique with purposive sampling. The data collection technique uses an online questionnaire via the Google form. Data analysis used Moderated Regression Analysis (MRA) processed with SPSS 25. The results of this study prove that green marketing influences green behavior, and consumer interest can strengthen the influence of green marketing on green behavior. Keywords: Green Marketing, Green Behavior, and Consumer Interest